2004
DOI: 10.1577/01-136
|View full text |Cite
|
Sign up to set email alerts
|

First‐Year Growth, Condition, and Size‐Selective Winter Mortality of Freshwater Drum in the Lower Missouri River

Abstract: We compared first‐year growth and relative condition (Kn) of the 1997 and 1998 year‐classes of freshwater drum Aplodinotus grunniens among three sites in a 235‐km reach of the channelized Missouri River and tested for the occurrence of size‐selective overwinter mortality during the first winter. Prewinter mean length was 15 mm greater, mean weight was 8 g greater, and mean Kn was 5% greater at the upstream site than at the downstream site. The prewinter mean length of age‐0 freshwater drum was significantly gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Similarly, Archer et al (2000) observed that growth of larval fishes was negatively related to abnormally high summer river discharges. Some studies (Toneys and Coble, 1979;Archer et al, 2000;Braaten and Guy, 2004) have suggested that smaller larval fishes in the fall might increase first-year winter mortality.…”
Section: Growthmentioning
confidence: 99%
“…Similarly, Archer et al (2000) observed that growth of larval fishes was negatively related to abnormally high summer river discharges. Some studies (Toneys and Coble, 1979;Archer et al, 2000;Braaten and Guy, 2004) have suggested that smaller larval fishes in the fall might increase first-year winter mortality.…”
Section: Growthmentioning
confidence: 99%
“…In fact, the projected change in climate could be beneficial by potentially allowing these fish to have more stable recruitment, grow faster, reach maturity more quickly, and reach larger maximum lengths. From a population standpoint, these findings suggest that Freshwater Drum populations along the Upper Mississippi River could increase in size due to having more stable recruitment and quicker growth rates, which increases chances of survival through their first winter of life (Braaten & Guy, ). Although these are simply predictions, they could become reality if future temperatures increase at the expected rates.…”
Section: Discussionmentioning
confidence: 99%
“…To partition the effects of potential growth and sizeselective mortality across the winter, we employed empirical quantile-quantile (QQ) and increment plots [15,40], a combined approach that has been applied to a variety of species [41][42][43][44][45]. For the QQ plots, total length at quantiles 1, 5, 10, 25, 50, 75, 90, 95, and 99 of the size distribution was determined from the length-frequency histograms (i.e., when n > 50; [46]) for the fall and subsequent spring samples, and were plotted against each other.…”
Section: Size-selective Overwinter Mortality and Growthmentioning
confidence: 99%